Fenomena Cadar Dalam Perspektif Mahasiswa Universitas Muhammadiyah Surabaya - Sholihul Huda; Iman Permadi (Al Hikmah, 2019)
AbstractThere were two formulations of the problem to be examined in this thesis, namely: (1) What is the view of Muhammadiyah University of Surabaya students towards the purdah phenomenon? (2) How is the typology of views of Muhammadiyah University of Surabaya students in interpreting the purdah phenomenon?To answer the research, this study used qualitative research methods. Then, the data obtained are presented in a descriptive form and analyzed using the Phenomenology and Sociology of Knowledge theory. To map the thoughts of students of the Muhammadiyah University of Surabaya, researchers described the phenomenon of multicultural Islamic thought Nurcholish Madjid.From the results of this study, it was found that there are 3 types of views: (1) Islamic-Transformative views. This view is owned by 6 of the 14 informants. They have concerns and are responsive to various actual problems that occur in society. Fourth, having an orientation in an effort to realize the ideals of Islam and society with a vision of mercy for all nature. (2) Islamic-Normative views, which depart from texts that are written in the holy book of each religion to certain limits with their characteristics namely; literalist, textual or scriptualist. (3) Liberal Islam views represent 4 out of 14 informants trying to ground and rationalize understanding of Islamic doctrine as rational religion and elasticity. This view basically requires how Muslims should understand Islam comprehensively starting from the aspects of monotheism, sharia, muamalat and ethics. Keywords: Purdah Phenomenon, Perspective, Students of Muhammadiyah University Surabaya